2012
DOI: 10.1021/mz3004192
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Responsive Disassembly of Polymersomes of Sequence-Specific Boroxole-Containing Block Copolymers under Physiologically Relevant Conditions

Abstract: Polymers containing organoboronic acids have recently gained interest as sugar-responsive materials owing to the reversible binding of saccharides to boronic acids, which triggers a change in the physical and chemical properties of these polymers, such as their water solubility. In particular, the ability of these polymers to bind glucose has attracted considerable attention because of the promise of these materials for the development of sensors and drug delivery systems for glucose-related human diseases, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 30 publications
0
77
0
Order By: Relevance
“…[3][4][5] Amongst these self-regulated insulin delivery systems, synthetic phenylboronic acid (PBA)-based polymeric materials with high stability have shown more promising applications than glucose oxidase (GOD) and lectin (Con A) based systems. [6][7][8] Until now, a variety of PBA-based glucose-responsive materials particularly in the form of nanoparticles including nanogels (microgels), [9][10][11] micelles, [12][13][14][15] vesicles, [16][17][18][19][20] and mesoporous silica nanoparticles 21,22 have been broadly explored and shown to exhibit effective glucose-responsiveness at physiological pH and reasonable glucose-sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Amongst these self-regulated insulin delivery systems, synthetic phenylboronic acid (PBA)-based polymeric materials with high stability have shown more promising applications than glucose oxidase (GOD) and lectin (Con A) based systems. [6][7][8] Until now, a variety of PBA-based glucose-responsive materials particularly in the form of nanoparticles including nanogels (microgels), [9][10][11] micelles, [12][13][14][15] vesicles, [16][17][18][19][20] and mesoporous silica nanoparticles 21,22 have been broadly explored and shown to exhibit effective glucose-responsiveness at physiological pH and reasonable glucose-sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…By performing an alternating copolymerization of styreneboroxoles with N -functionalized maleimides, various PEG containing block copolymers were synthesized that formed uniform polymersomes in both neutral buffer and serum (Figure 5). Due to the nature of the polymersomes, water-soluble drugs can be contained and shielded within the aqueous environment of the self-assembled core without the need for chemical modification [47]. …”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…Moreover, the functional group tolerance is generally higher as the need for reactive borane species such as BBr 3 or transition metal catalysts can be circumvented. This allows for a greater variety of other functional comonomers to be incorporated, including acrylates, acrylamides, vinylpyridines, and ethylene oxide [39][40][41][42][43][44]. However, the polymerizability of each new monomer has to be investigated and the polymerization conditions carefully optimized.…”
Section: Direct Polymerization Of Borane Monomers By Chain Growth Metmentioning
confidence: 99%
“…In a different approach, Kiser and coworkers incorporated more acidic boroxoles [139,140] into polymer structures [141][142][143][144]. Related block copolymers (55,56) were investigated by Kim and coworkers as building blocks of responsive vesicles for insulin release applications [36,40]. Narain and coworkers found that the combination of boroxolefunctionalized polyacrylamide copolymer 57 with glycopolymers resulted in temperature-, pH-, and glucose-responsive gels [39].…”
Section: Boronic and Borinic Acid-functionalized Polymers For Biomedimentioning
confidence: 99%